An ultrastructural study in a case of Wolman’s disease (Clinical, Biochemical, Light and Electron Microscopic Study) - Özoran, Yavuz; Özoran, Afet; Kerse, İlhan and Gürgey, Aytemiz and Özsoylu, Şinasi and Koçak, Nurten and Ciliv, Gönenç (The Turkish Journal of Pediatrics, 1978)
The ultrastructural studies of liver and spleen in a case of Wolman’s disease are reported. Lipid accumulation in parenchymal cells, and cholesterol crystal clefts in Kupffer cells were observed in the liver. Lipid deposited macrophages (foam cells) were observed in the spleen.